Cloning of oligopeptide transport carrier PepT2 and comparative analysis of PepT2 expression in response to dietary nitrogen levels in yak and cattle - ZHAO, ZHIWEI; SHI, FUYU; WANG, HUCHENG (The Indian Journal of Animal Sciences, 2021)
The objectives of this study were clone oligopeptide transport carrier PepT2 and compare its abundance in kidney tissues of yak and cattle in response to different dietary nitrogen levels. Four adult female yaks were enrolled as donor animals for profiling the molecular characteristics and expression specificity of yak PepT2 (yPepT2), and twenty-four castrated males of each of two genotypes, yak (Bos grunniens) and indigenous cattle (Bos taurus) were used to explore PepT2 mRNA expression in kidney tissue in different nitrogen (N) levels (10.3, 19.5, 28.5 or 37.6 g N/kg dry matter; DM). Our results showed that the yPepT2 coding sequence region contains 2190 bp, and encodes a putative protein of 729 amino acids (AA) residues. The yPepT2 AA sequence identified eight putative extracellular N-glycosylation sites (Asn7, Asn80, Asn373, Asn435, Asn472, Asn508, Asn528, Asn587) and eight intracellular putative protein kinase C sites (Ser34, Ser264, Ser274, Ser376, Ser442, Ser586, Ser640, Ser724). The yPepT2 AA sequence was 98 and 94% identical to PepT2 from zebu cattle (Bos indicus) and sheep (Ovis aries), respectively. The relative PepT2 expression in kidney tissue for yak was greater than of indigenous cattle in the10.3 and 28.5 N/kg DM diet, but it was lower for yaks in 37.6 N/kg DM diet. These implied that relative PepT2 mRNA expression was higher in yak kidney than that in indigenous cattle at lower dietary N supplies, but more research on PepT2 will be required to determine the renal regulatory mechanisms.